O programa Brasil profissionalizado em cena: O Estado de Alagoas como palco - Silva, Camila Ferreira da (2014)
Enter and leave the scene various public policies for the education of brazilian workers each new government. What they have in common element, in addition to any possible approaches immediacy, is the capacity to reveal - when analyzed – the perspectives that underpin each. These perspectives are, in turn, transformed into real clues to researchers who propose to understand the whys surrounding the performance of the national State under Professional education (as well as in many other areas). This dissertation of master's degree fits into this context as another vehicle for analysis of a specific public policy for the education professional. The Program Professionalized Brazil stepped in the fifth year of the Lula da Silva government (through Decree Nº. 6302 of 2007), and, since then, according to their main purpose, has marked the numerous attempts to integrate the high school to vocational education in the states of the federation. This program was taken, therefore, the analysis in the present investigation under the following problem: to what extent the materialization Program Professionalized in Alagoas, between 2007 and 2011, contributed to the strengthening of the public offering professional education and that levels of this type of education were privileged? Considering this timeframe and the program mentioned here, the main objective of the research was to analyze the materialization of Professionalized Brazil in the state of Alagoas, in view of the announced elements in the problem. For this, the methodological apparatus selected to guide our investigation course was the qualitative approach combined with the explanatory research type from a critical perspective. The methodological approach included the following steps: literature review; collection of documentary material; collection / production data by fieldwork (focusing on interviews with the subject directly involved with the management of Brazil Professionalized in Alagoas); treatment and analysis of data, based on the technique of content analysis, both to documents, and to the corpus of interviews. The understanding of the processes of planning, implementation and evaluation of Professionalized Brazil in the state of Alagoas was an exercise that allows us: the one hand, to understand the shy impact of this program when it comes to overcoming historical issues surrounding the professional education in this state and, on the other, to recognize the entering and exiting the scene of so many programs (and projects, plans, goals, etc.). distinct as the main expression of the performance of the Brazilian state within the work-education connection in contemporary Brazil and their disputes historically constructed.